SAT0219 Efficacy and safety of atacicept in patients with high disease activity in a 24-week, randomized, placebo-controlled, phase iib study (ADDRESS II). (15th June 2017) - Merrill, JT; Wallace, DJ; Kao, A; Mateo, C Vazquez; Fraser, PA; Chang, P; Isenberg, D
Abstract : Background: Atacicept targets B-cell stimulating factors BLyS and APRIL, and has shown evidence of clinical response in SLE. Objectives: Exploration of atacicept efficacy and safety in a pre-defined subpopulation of SLE patients with high disease activity (HDA, SLEDAI-2K ≥10 at Screening) in the phase IIb ADDRESS II study (NCT01972568 ). Methods: Autoantibody positive patients on standard of care therapy were randomized 1:1:1 to double-blind weekly SC injections of atacicept 75 or 150 mg or placebo (PBO) for 24 weeks. Analyses of the HDA subpopulation are now reported. Results: 52% of the ITT population had HDA (n=158: 52 PBO; 55 atacicept 75 mg; 51 atacicept 150 mg). 92% were female, 67% were white, and baseline characteristics were balanced between groups. At week 24 (Table 1 ; Figure 1 ), the proportion of SLE Responder Index (SRI)-4 (p<0.05) and SRI-6 (p<0.005) responses was greater with atacicept 150 mg vs PBO. BICLA response rate was higher with both doses (p<0.05). More patients achieved SLEDAI-2K ≤2 with atacicept 150 mg vs PBO (p<0.01). Time to severe and moderate-severe flare was significantly reduced at both atacicept doses vs PBO (p<0.05). Patients in the quartile with the largest decline in serum IgG had the highest SRI-6 response rates (Table 2 ). Treatment-emergent adverse event (TEAE) rates were similar between groups (PBO 71.2%; 75 mg 78.2%; 150 mg 74.5%). Serious/severe infections were not increased with atacicept 150 mg (PBO 9.6%; 75 mg 10.9%; 150 mg 0%). There were no patient deaths. Conclusions: In SLE patients with HDA, Atacicept 150 mg demonstrated significant clinical responses and an acceptable safety profile. Acknowledgements: The study was sponsored by EMD Serono Research & Development Institute Inc., USA (a business of Merck KGaA, Germany). Medical writing support was provided by Bioscript Science, UK, and funded by Merck KGaA. Disclosure of Interest: J. Merrill Consultant for: received consulting fees from Anthera Pharmaceuticals, Lilly, EMD Serono, GlaxoSmithKline and Biogen, D. Wallace Consultant for: received consulting fees from EMD Serono, A. Kao Employee of: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, C. Vazquez Mateo Employee of: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, P. Fraser Employee of: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, P. Chang Employee of: EMD Serono Research & Development Institute, Inc. (a business of Merck KGaA, Darmstadt, Germany), Billerica, MA, USA, D. Isenberg Consultant for: received consulting fees from EMD Serono